Scaling Deep the Child to Child Approach to Ease Transition From Pre-primary to Lower Primary in Uganda, Ethiopia and Malawi (Journal of Education and Development, 2024)
Background: Children benefit more from education if they are helped to transit from one level to another. Different strategies are always suggested and sometimes implemented to novel ideas that can promote transition, but with limited effort at scaling. The Child to Child Approach is one such approach that has been used to support the transition of children from pre-primary to early grade primary school. However, limited efforts have been made to support deep scaling, as most focus on just the interventions. Aim: This paper highlights strategies that were used to scale deep the Child to Child approach to support the transition of children from pre-primary to lower primary in selected districts in Uganda, Malawi and Ethiopia. Setting: This paper is based on the current situation where many interventions are being implemented in specific areas but are never scaled in marginalized communities to leverage impact. Methods: A reflective approach, field reports and a desk review were used to collect data. Results: Different strategies are highlighted including identifying and dealing with scaling deep concerns, engagement of relevant stakeholders at community, district and national levels and working with authorities in the area to endorse the approach worked best to settle the deep cultural uncertainties about scaling. Conclusion: Implementers need to identify scaling deep bottlenecks early and work to solve them before embarking on scaling approach. Contribution: This paper contributes to knowledge on what stakeholders who need to scale child to child programmes have to take into consideration for sustainability of their initiatives.